Dexamethasone Alleviates Myocardial Injury in a Rat Model of Acute Myocardial Infarction Supported by Venoarterial Extracorporeal Membrane Oxygenation - Xingdong Cheng; Rongzhi Zhang; Shilin Wei; Jian Huang; Kerong Zhai; Yongnan Li; Bingren Gao (Frontiers Media S.A., 2022)
Myocardial ischemia causes myocardial inflammation. Research indicates that the venoarterial extracorporeal membrane oxygenation (VA ECMO) provides cardiac support; however, the inflammatory response caused by myocardial ischemia remains unresolved. Dexamethasone (Dex), a broad anti-inflammatory agent, exhibits a cardioprotective effect. This study aims to investigate the effect of Dex on a rat model of acute myocardial infarction (AMI) supported by VA ECMO. Male Sprague-Dawley rats (300-350 g) were randomly divided into three groups: Sham group (n = 5), ECMO group (n = 6), and ECMO + Dex group (n = 6). AMI was induced by ligating the left anterior descending (LAD) coronary artery. Sham group only thoracotomy was performed but LAD was not ligated. The ECMO and ECMO + Dex groups were subjected to 1 h of AMI and 2 h of VA ECMO. In the ECMO + Dex group, Dex (0.2 mg/kg) was intravenously injected into the rats after 1 h of AMI. Lastly, myocardial tissue and blood samples were harvested for further evaluation. The ECMO + Dex group significantly reduced infarct size and levels of cTnI, cTnT, and CK-MB. Apoptotic cells and the expression levels of Bax, Caspase3, and Cle-Caspase3 proteins were markedly lower in the ECMO + Dex group than that in the ECMO group. Neutrophil and macrophage infiltration was lower in the ECMO + Dex group than in the ECMO group. A significant reduction was noted in ICAM-1, C5a, MMP-9, IL-1β, IL-6, and TNF-α. In summary, our findings revealed that Dex alleviates myocardial injury in a rat model of AMI supported by VA ECMO.